2010
DOI: 10.1577/h09-019.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distribution of the Asian Fish Tapeworm Bothriocephalus acheilognathi (Cestoda: Bothriocephalidea) in the Rio Grande (Río Bravo del Norte)

Abstract: Recent collections of the Asian fish tapeworm Bothriocephalus acheilognathi in the Rio Grande have raised concern about the potential impacts on Rio Grande endemic and imperiled fishes. The objectives of this study were to determine distribution and definitive hosts of the Asian fish tapeworm within the Rio Grande drainage and to quantify occurrences and abundances. In total, 1,992 fish spanning 11 families were collected and examined for Asian fish tapeworms in the Rio Grande and the Pecos and Devils rivers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(32 reference statements)
0
3
0
1
Order By: Relevance
“…A generalist parasite strategy is advantageous during changes in host availability during an invasion, and generalist parasites may quickly become independent of their native hosts. For example, a fishparasitising cestode from East Asia, Bothriocephalus acheilognathi, was introduced globally by the intercontinental export of carp species and now has exploited many native fish species in its novel range, causing significant economic losses in fisheries worldwide (e.g., Bean and Bonner 2010;Brouder and Hoffnagle 1997). We predict that A. woodiana has the potential to invade areas outside the range of their co-invasive native hosts, even if their initial invasion was likely facilitated by the presence of their native hosts.…”
Section: Invasion Potential Of a Woodianamentioning
confidence: 99%
“…A generalist parasite strategy is advantageous during changes in host availability during an invasion, and generalist parasites may quickly become independent of their native hosts. For example, a fishparasitising cestode from East Asia, Bothriocephalus acheilognathi, was introduced globally by the intercontinental export of carp species and now has exploited many native fish species in its novel range, causing significant economic losses in fisheries worldwide (e.g., Bean and Bonner 2010;Brouder and Hoffnagle 1997). We predict that A. woodiana has the potential to invade areas outside the range of their co-invasive native hosts, even if their initial invasion was likely facilitated by the presence of their native hosts.…”
Section: Invasion Potential Of a Woodianamentioning
confidence: 99%
“…by humans, birds, oods etc) to adjacent lentic or lotic systems, this parasite would pose a serious threat to the unique freshwater (and possibly estuarine) sh fauna of south-western WA. Several studies have already shown that AFT can infect sh in environments with low to moderate salinity (Ozturk et al 2002;Bean 2008;Bean and Bonner 2010;İnnal et al 2016;Sara et al 2016;McAllister et al 2017;Güven and Öztürk 2018;Zhokhov et al 2019), and has already threatened the populations of several endemic species in other countries (Salgado-Maldonado and Pineda-López 2003;Choudhury et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…to adjacent lentic or lotic systems, this parasite would pose a serious threat to the unique freshwater (and possibly estuarine) fish fauna of south-western WA. Several studies have already shown that AFT can infect fish in environments with low to moderate salinity (Ozturk et al, 2002;Bean, 2008;Bean & Bonner, 2010;İnnal et al, 2016;Sara et al, 2016;McAllister et al, 2017;Güven & Öztürk, 2018;Zhokhov et al, 2019), and has already threatened the populations of several endemic species in other countries (Salgado-Maldonado & Pineda-López, 2003;Choudhury et al, 2006Choudhury et al, , 2013de León et al, 2018).…”
Section: Discussionmentioning
confidence: 99%